Uso de herramientas tecnológicas del turista de la provincia de Cotopaxi, en confinamiento. - Bautista Ronquillo, Wilinton Alexis (2023)
The present research project was carried out with the purpose of buying the use of technological tools by tourists in the province of Cotopaxi before and after confinement, for which a longitudinal investigation was carried out with a quantitative approach, with a comparative relational scope, the same whose main objective was to compare these variables through the implementation of the sampling instrument, referring to the surveys carried out in the attractions, taking as a reference the characterization of 11 attractions in the province of Cotopaxi, differentiated into 7 cantons. With the survey carried out, there were 3 study variables to be able to determine (frequency, expense and type) for the respective analysis, through the statistical program of the SPSS that helped to extract and analyze the most relevant data for the correct decision making of efficiency, resulting in a notorious change in spending, use and spending, which helped the application of the Wilconxon statistical test, a program to determine ranges to the statistics of the study variable, where statistical groups of greater than minor, to obtain the statistical data of contrast, as well as data of positive, negative and tied statistics. Where it was observed that the study variables were accepted so that there is a change, where the type of tool according to the singularity is 0.086, being a range greater than 0.05%, being a noticeable change in the use of technological tools such as the cell phone, computer and the different digital platforms, while in the variables of use and expense there were surpluses of less than 0.5%, having a significant change since the surpluses of use exceeded 7 hours of use in the same way, the Expenses equaled more than 30% for the determined number of respondents, conclusively tourists focus on technological tools and this becomes a positive for the different tourist places that the province of Cotopaxi offers, for this reason it is considered to encourage the use of technological tools in the digitization of data that contain accurate and concise information for the distribution of important data on tourist attractions.